Bibliometric visual analysis of the poly(vinylidene fluoride–trifluoroethylene) piezoelectric nanomaterial: research history, hotspots, and developmental trend - Chen, Zhiguang; He, Wen; Zhang, Wei (Frontiers in Materials, 2023)
Introduction: Poly(vinylidene fluoride-trifluoroethylene) [P(VDF-TrFE)] stands out as an organic polymer with remarkable piezoelectric properties, coupled with high chemically stability and biocompatibility, rendering it the most promising organic piezoelectric nanomaterial. Therefore, we aim to explore its developmental history, find current research hotspots, and identify emerging trends. Methods: To comprehensively review the pertinent literature on poly(vinylidene fluoride-trifluoroethylene) or P(VDF-TrFE) in English from 1992 to 2022, we utilized the Web of Science Core Collection. Additionally, bibliometric tools such as CiteSpace, VOSviewer, Bibliometrics online analysis platforms (https://bibliometric.com), along with SCImage graphics, were employed to delineate historical features, track the evolution of active topics, and identify emerging trends on the P(VDF-TrFE) field. Results: The annual publication and citation counts for articles on P(VDF-TrFE) have exhibited consistent growth since 1992, with Asia, notably China, contributing the highest number of publications on P(VDF-TrFE) materials. Interestingly, researchers in the United States demonstrated the most robust international collaborations across various countries. Keywords were categorized into nine clusters: 0# vinylidene fluoride, 1# thin-film transient, 2# energy harvesting, 3# dielectric property, 4# thin film, 5# film, 6# mobile modeling, 7# growth, and 8# pyroelectric sensor. The performance of constituent materials in electronic energy-storage applications and current and future research in nanofields, including nanofilms, nanofibers, and nanogenerator, are considered hotspots and developmental trends, respectively. Among the most cited articles, these articles are commonly related to PVDF and P(VDF-TrFE) ferroelectricity. Conclusion: Therefore, we believe that the electromechanical coupling performance of P(VDF-TrFE) and the research in nano fields is research hotspot that will trend into the future.